2020
DOI: 10.1093/nar/gkaa041
|View full text |Cite
|
Sign up to set email alerts
|

Complex impact of DNA methylation on transcriptional dysregulation across 22 human cancer types

Abstract: Accumulating evidence has demonstrated that transcriptional regulation is affected by DNA methylation. Understanding the perturbation of DNA methylation-mediated regulation between transcriptional factors (TFs) and targets is crucial for human diseases. However, the global landscape of DNA methylation-mediated transcriptional dysregulation (DMTD) across cancers has not been portrayed. Here, we systematically identified DMTD by integrative analysis of transcriptome, methylome and regulatome across 22 human canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…Although inverse correlation between promoter methylation and gene expression has been observed in different tissues [ 32 ], the exact regulatory role of methylation on transcriptome has yet to be uncovered [ 33 ]. In particular, transcriptional regulation by methylation in cancer has been shown to be a complex molecular mechanism, characterized by the intricate interplay between SNPs, transcription factors and DNA methylation in regulating gene expression [ 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although inverse correlation between promoter methylation and gene expression has been observed in different tissues [ 32 ], the exact regulatory role of methylation on transcriptome has yet to be uncovered [ 33 ]. In particular, transcriptional regulation by methylation in cancer has been shown to be a complex molecular mechanism, characterized by the intricate interplay between SNPs, transcription factors and DNA methylation in regulating gene expression [ 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is an epigenetic modification that plays a crucial role in regulating the growth, development, gene expression pattern, and stability of the genome without changing the DNA sequence [12,13]. Many studies in recent years have found that abnormal DNA methylation is closely related to tumorigenesis, development, and cell canceration [14][15][16]. In particular, alterations in DNA methylation can supply crucial information for the early diagnosis and prognosis of cancer [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…All patients with glioma were divided into a training set and a testing set of similar gender and age. We next used the Cox hazard analysis to identify the genes associated with survival 32 , 33 . Genes with p < 0.05 were identified based on the expression profiles in the training set.…”
Section: Methodsmentioning
confidence: 99%